Canon 1096 on ignorance: Application to tribunal and pastoral practice. - Sherba, Girard Michael. (University of Ottawa (Canada), 2001)
Before Vatican II, marriage was often considered, or at least popularly expressed, as a union of bodies; that is to say, marriage was an exclusive contract by which a man and a woman mutually handed over their bodies for the purpose of acts which led to the procreation of children. Matrimonial jurisprudence was primarily focused on this marital contract. With the advent of Vatican II and its emphasis on the personalist notion of marriage, a new age dawned whereby canonists, especially auditors of the Roman Rota, were henceforth to view marriage as a union of persons. "Person" is more than a "body"; rather, a person is an individual consisting of wants, needs, desires, impulses, hopes and dreams, whose life experience has been shaped by the milieu---cultural, familial, religious---from which he or she comes. "Union" is not only simply understood as a "contract", but also is now once again recognized as a "covenant", a concept which, at least in the Latin Church, was prevalent until the 12th century. One of the canons of the 1983 CIC, although almost identical in wording to its predecessor in the 1917 CIC, but which now must be understood and interpreted in light of the teachings of Vatican II, is canon 1096 which pertains to the effect of ignorance on matrimonial consent. Given the current appreciation of marriage founded in the teachings of Vatican II, especially in Gaudium et spes, reiterated by Popes Paul VI and John Paul II and described in the Catechism of the Catholic Church, complicated by today's western society's stress on individualism and permeated by a divorce mentality, what is the impact of this canon on matrimonial consent? How can its meaning, once understood as being wider than merely the sexual act itself, be better utilized by those in tribunal ministry? This is the major thrust of the present work. The research of the history and development of the concept of ignorance in canonical writings, how its understanding broadened especially after Vatican II and our conclusions on how to apply its richness to marriage nullity led us to expand the use of this canon: how it can aid in the development of pre-marital preparation programs which would not only possibly help prevent couples from being ignorant of the essence of marriage but also help them to appreciate this richness more deeply in their own lives so that marriage truly can become, as we read in canon 1055, "a partnership of the whole of life which is ordered by its nature to the good of the spouses and the procreation and education of offspring". It is our sincere hope that this study will be of benefit to all who read it.
Keywords: History, Church.